PENILAIAN PRESTASI KERJA KARYAWAN PT. PERKEBUNAN NUSANTARA IV MEDAN DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Winda Risfani Nst; Sajaratud Dur; Hendra Cipta (UIN Sumatera Utara Medan, 2023)
Employee performance appraisal is one of the important roles in the company. This is done to evaluate, motivate and improve employee performance in the company. The results of this performance are used to determine employees who excel. This study uses 5 criteria, namely commitment, integration, professional, innovative, and disciplined. Simple Additive Weighting (SAW) is used to determine the weight value of each attribute, followed by ranking to select each given alternative. This method can help decision making to produce the greatest value as the best alternative. This research was conducted on 37 respondents' data. The results of the study indicate that this can provide the best decision alternative in making decisions to assess employee performance.